Chronic stress in myofascial pain patients - Schmitter, Marc; Keller, Livia; Giannakopoulos, Nikolaos Nikitas; Rammelsberg, Peter (Clinical oral investigations, 2010)
Although myofascial pain has often been described as being associated with psychosocial stress, detailed evidence in support of this assumption, either from standardized clinical examination or from validated chronic stress questionnaires, is absent. The hypothesis of the present study was that some stressors lead to higher scores in patients suffering from chronic myofascial pain than in pain-free controls and in patients suffering from chronic facial pain. One hundred and fifty subjects were included in the study, and depending on clinical findings, divided into three groups: exclusively chronic myofascial pain group, controls with chronic facial pain but without temporomandibular disorders (TMD), and controls without pain or TMD. Chronic stress was assessed on nine subscales by use of a validated questionnaire. Myofascial pain patients have a significantly higher stress score for “social isolation” than pain-free controls (t-test, p = 0.003). However, they do not have higher scores than patients suffering from facial pain (t test, p = 0.169). Thus, the hypothesis of this study could not be completely rejected.